2008
DOI: 10.1177/0739986308318713
|View full text |Cite
|
Sign up to set email alerts
|

Family Cohesion and Its Relationship to Psychological Distress Among Latino Groups

Abstract: This paper presents analyses of a representative sample of US Latinos (N=2540) to investigate whether family cohesion moderates the effects of cultural conflict on psychological distress. The results for the aggregated Latino group suggests a significant association between family cohesion and lower psychological distress and the combination of strong family cohesion with presence of family cultural conflict was associated with higher psychological distress. However, this association differed by Latino groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
225
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(241 citation statements)
references
References 36 publications
13
225
2
1
Order By: Relevance
“…In these studies, the emphasis has been on normative confl ict over "minor" everyday issues (Laursen et al, 1998;Smetana, 1988). In contrast, studies of parent-adolescent confl ict involving immigrant families of Asian and Latino heritage have primarily focused on disruptive confl ict over more "serious" issues concerning core cultural values, namely, acculturation-based confl ict (Portes & Rumbaut, 1996, 2001Rivera et al, 2008). Less is known about whether acculturationbased confl ict is normative and whether it is a healthy part of youth development.…”
Section: Family Conflict Among Chinese-and Mexican-origin Adolescentsmentioning
confidence: 89%
“…In these studies, the emphasis has been on normative confl ict over "minor" everyday issues (Laursen et al, 1998;Smetana, 1988). In contrast, studies of parent-adolescent confl ict involving immigrant families of Asian and Latino heritage have primarily focused on disruptive confl ict over more "serious" issues concerning core cultural values, namely, acculturation-based confl ict (Portes & Rumbaut, 1996, 2001Rivera et al, 2008). Less is known about whether acculturationbased confl ict is normative and whether it is a healthy part of youth development.…”
Section: Family Conflict Among Chinese-and Mexican-origin Adolescentsmentioning
confidence: 89%
“…Indeed, studies using the NLAAS data have found mental health benefits of family cohesion (Rivera et al, 2008). On the other hand, family cohesion may hinder healthy behaviors, for instance, through individuals prioritizing other family members' needs over their own well-being (Perez & Cruess, 2014).…”
Section: Family Cohesionmentioning
confidence: 99%
“…Hispanic cultural values are thought to protect against external stress, to discourage family conflict, and to promote a strong orientation toward the family (Gonzales, Deardorff, Formoso, Barr, & Barrera, 2006;Rivera et al, 2008). With acculturation, youth may disengage from, or not learn about, these protective cultural values, thereby increasing their smoking risk (Gil, Wagner, & Vega, 2000).…”
Section: Hispanic Cultural Valuesmentioning
confidence: 99%